Fluxos de tecidos foliares e padrões de desfolhação em pastagem de papuã sob pastejo de novilhas recebendo níveis de suplemento energético - Severo, Paula de Oliveira (2016)
The work was carried out to evaluate the defoliation patterns and quantify the leaf tissue flows in Alexandergrass, grazed by beef heifers in different feeding systems, in rotational grazing method. The experimental design was completely randomized with repeated measures, three levels of supplementation with whole rice bran (0; 0.5 and 1% of body weight) and two area replications. The supply of whole rice bran for heifers grazing in Alexandergrass allows can increase 13% the stocking rate. The leaf tissue flows, consumption of leaf blades and the grazing intensity are not changed by supplement. Regardless of the system feeding the heifers graze the leaf blades growing in a smaller period of time compared to other types of leaf, which allows the leaf crop top extract canopy.